2013
DOI: 10.1080/09537287.2013.780313
|View full text |Cite|
|
Sign up to set email alerts
|

Value creation through collaborative supply chain: holistic performance enhancement road map

Abstract: International audienceThis paper proposes an integrated framework to analyse Business-to-Business relationships using data mining techniques such as K-Means based on particle swarm intelligence (PSO) and Association Rule (AR). It constructs relationship rules of holistic performance enhancement road map. The data set of relationships between enterprise and its direct customers was used for demonstration. The results of the case study in France show, how domain managers powerfully use the graphical analysis res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…To address fragmentation, Chouinard et al (2009) elaborated a CLSC framework for the design and management of value loops highlighting key capabilities and organisational requirements in marketing, design, logistics and operations. Holimchayachotikul, Derrouiche, Damand, and Leksakul (2014) amongst others stressed the importance of collaboration, although observing that integrating value creation and recovery activities requires "overcome[ing] the old paradigm of competing as independent entities" (Hofmann & Locker, 2009, p. 79). The combination of value cycles and collaboration equates to Porter and Kramer's (2011, p. 52) concept of shared value achieved via reconceiving products and markets, redefining productivity in the value chain, and building supportive industry clusters at the company's locations.…”
Section: Value Creation Clsc and The Circular Economymentioning
confidence: 99%
“…To address fragmentation, Chouinard et al (2009) elaborated a CLSC framework for the design and management of value loops highlighting key capabilities and organisational requirements in marketing, design, logistics and operations. Holimchayachotikul, Derrouiche, Damand, and Leksakul (2014) amongst others stressed the importance of collaboration, although observing that integrating value creation and recovery activities requires "overcome[ing] the old paradigm of competing as independent entities" (Hofmann & Locker, 2009, p. 79). The combination of value cycles and collaboration equates to Porter and Kramer's (2011, p. 52) concept of shared value achieved via reconceiving products and markets, redefining productivity in the value chain, and building supportive industry clusters at the company's locations.…”
Section: Value Creation Clsc and The Circular Economymentioning
confidence: 99%
“…Two studies have focused on the co-creation of business value (Holimchayachotikul, Derrouiche, Damand, & Leksakul, 2013;Maguire, et al, 2012). In an experimental study in France, Holimchayachotikul et al (2013) introduced the concept of measuring value along the supply chain from a collaborative and balanced scorecard (BSC) perspective in the business-to-business (B2B) context.…”
Section: Transformational Business Valuementioning
confidence: 99%
“…In an experimental study in France, Holimchayachotikul et al (2013) introduced the concept of measuring value along the supply chain from a collaborative and balanced scorecard (BSC) perspective in the business-to-business (B2B) context. Their findings suggested that managers heavily utilized graphical analysis results to improve holistic performance.…”
Section: Transformational Business Valuementioning
confidence: 99%
“…In other words, the value is not determined by the service provider, but by the user after experiencing the commodities and services [1,2]. There may be a considerable gap between the 'service end' and 'customer end' regarding perceptions about the commodity and service value.…”
Section: Introductionmentioning
confidence: 99%
“…Validi et al [34] employed the MOPSO optimizer to eliminate unrealistic solutions, using a popular multi-attribute decision-making approach to evaluate the solutions within the Pareto optimal solution space. Hung and Maleki [4] applied group technology to the forging operations of the Tabriz Tractor Manufacturing Industry, and Holimchayachotiku et al [1] introduced the innovative idea of measuring value added along the supply chain using a collaborative method. Jamian et al [35] solved a series of complex problems using global PSO, and Jakubcová et al [36] found a better modification of the PSO algorithm using adaptive inertia weights.…”
Section: Introductionmentioning
confidence: 99%